2016
DOI: 10.1016/j.rmed.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled multicentric study of inhaled budesonide and intravenous methylprednisolone in the treatment on acute exacerbation of chronic obstructive pulmonary disease

Abstract: Results show that inhalation of budesonide (2 mg 3 times/day) and systemic methylprednisolone (40 mg/day) had similar clinical outcome in AECOPD. In conclusion, inhaled budesonide is an alternative to systemic corticosteroids in AECOPD treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 32 publications
4
72
0
2
Order By: Relevance
“…rcjournal.com]). Of these, 9 prospective studies, 15,[26][27][28][29][30][31][32][33] which involved nearly 1,000 subjects hospitalized for COPD exacerbations, were included in the meta-analysis, however, depending on the specific analysis, fewer subjects were included. The only study conducted in the outpatient setting did not meet study criteria for inclusion in our analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…rcjournal.com]). Of these, 9 prospective studies, 15,[26][27][28][29][30][31][32][33] which involved nearly 1,000 subjects hospitalized for COPD exacerbations, were included in the meta-analysis, however, depending on the specific analysis, fewer subjects were included. The only study conducted in the outpatient setting did not meet study criteria for inclusion in our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28]30,32,33 Despite the relatively large number of subjects included in these trials, not all the studies reported the outcomes of interest, and, therefore, a smaller number of subjects were involved in some of the individual outcomes. Notably, most studies excluded patients who had recent use of prednisone, 26,27,30,33 required admission to an ICU, 26,27,31,33 or had an exacerbation within 30 d of admission. 30,32,33 Overall, the quality of the included trials was low to moderate; results for the risk of bias are shown in Appendix 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…En varios ensayos clínicos aleatorizados [38][39][40] se ha evaluado la utilidad de la budesonida nebulizada a dosis altas (2 mg, 3 o 4 veces al día) frente a placebo en pacientes con EPOC hospitalizados por agudización moderada-grave no acidótica y han demostrado mejoría del FEV 1 tras broncodilatación y de la PaO 2 (presión arterial de oxígeno). En ambos casos se ha demostrado que este tratamiento puede ser una alternativa eficaz y segura, aunque más cara, a los corticoides orales cuando se produce una exacerbación de la EPOC.…”
Section: Corticoides Inhaladosunclassified